(untitled) (gjstudies, 2024)
This research investigates the complex relationship between accounting regulationcompliance, enforcement mechanisms, and financial reporting quality through a novelmethodological framework that integrates computational linguistics, network analysis,and evolutionary game theory. Departing from traditional econometric approaches thattreat compliance as a binary variable, we conceptualize compliance as a multidimensional spectrum influenced by regulatory complexity, corporate governance structures,and enforcement ecosystem dynamics. Our methodology employs a hybrid approachcombining natural language processing of regulatory documents, agent-based modeling of compliance behavior, and longitudinal analysis of enforcement actions acrossmultiple jurisdictions from 1995 to 2004. We introduce the Regulatory ComplianceIndex (RCI), a composite measure that captures both formal adherence to rules andsubstantive alignment with regulatory intent. The study examines how variationsin enforcement intensity, regulatory design characteristics, and corporate adaptationstrategies collectively shape reporting quality outcomes. Our findings reveal non-linearrelationships between enforcement severity and reporting quality, with diminishingreturns beyond optimal enforcement thresholds. We identify three distinct compliance archetypes—procedural, substantive, and strategic—each associated with different reporting quality outcomes. The research contributes to regulatory theory bydemonstrating how regulatory complexity interacts with enforcement capacity to produce unintended consequences, including compliance ritualism and creative compliancestrategies. Our results suggest that reporting quality is maximized not through maximal enforcement but through targeted interventions that address specific compliancebarriers and promote substantive rather than procedural adherence. This study offerspractical insights for regulators seeking to design more effective compliance ecosystemsand provides a novel analytical framework for future research on regulatory effectiveness.